The Cultural Transformation of Tumbilotohe in Responding to the Changing Times: a Case Study in Gorontalo City (International Journal of Education and Literature, 2025)
research discusses the transformation of Tumbilotohe culture in Gorontalo City as a response to the dynamics of the times and technological advancements. Tumbilotohe, which initially was a tradition of lighting oil lamps to mark the end of Ramadan, now experiencing significant changes in form, meaning, and implementation. This study uses qualitative approach with case study method, relying on in-depth interviews, observation, and documentation to explore the community's perceptions of the changes. The research results show that although the spiritual substance of Tumbilotohe remains maintained, its visual and technical aspects have been modernized through the use of electricity, digital ornaments, and decorative light shows. This transformation is influenced by technological developments, demands of the creative economy, and efforts to preserve culture in a more appealing form for the younger generation. This research emphasizes that culture dynamic and adaptive, as well as the importance of collaboration between society and the government in maintaining traditional values amidst the tide of modernization.